A discussion on the potential impact of residential radon exposure on the quality of exposure and risk assessment for former uranium miners - Chen, Jing (Radiation and environmental biophysics, 2021)
Epidemiological evidence of lung cancer risk from radon is based mainly on studies of underground miners where occupational exposures were, historically, relatively high in comparison to residential indoor exposure. However, radiation protection measures have caused radon levels in uranium mines to decrease significantly in more recent periods. Miners' occupational exposure is limited to their working years while they are exposed to environmental radon at home over their entire lifetime. Even during their limited working years, workers spend much more time at home than in workplaces. The biological effect of radon in mines cannot be distinguished from the biological effect of residential radon. Therefore, for an exposure-risk relationship study of former uranium miners, excess radon-induced lung cancer cases should be related to the combined radon exposure cumulated in workplaces and at homes in excess of the radon exposure of the reference population. This is especially important when residential radon levels differ or vary significantly between miners and the reference population over the course of extended follow-up years. This paper reviews some recent studies on former uranium miners, shares what seems controversial to the author and wonders whether lifetime exposure at home to widely varying radon concentrations can actually impact the quality of exposure assessment, and hence impact the results of the exposure-risk relationship.
Keywords: Radon; Radon-222; hodnocení rizik; Male; France; Risk Assessment; Occupational Exposure; Neoplasms, Radiation-Induced; Occupational Diseases; radioaktivní látky znečišťující vzduch; Česká republika; nádory vyvolané zářením; nemoci z povolání; pracovní expozice; Uranium; Adult; Mining; Exposure assessment; Aged; dospělí; Francie; senioři; mužské pohlaví; bydlení; Czech Republic; hornictví; senioři nad 80 let; lidé; Humans; radon; Housing; Air Pollutants, Radioactive; Aged, 80 and over; Risk assessment; Uranium miners; znečištění vzduchu ve vnitřním prostředí; lidé středního věku; Air Pollution, Indoor; uran; Middle Aged